Impairment of renal steroidogenesis at the onset of diabetes - Pagotto, Melina Andrea (2021)
Accumulating evidence indicates the association between changes in circulating sex steroid hormone levels and the development of diabetic nephropathy. However, the renal synthesis of steroid hormones during diabetes is essentially unknown. Male Wistar rats were injected with streptozotocin (STZ) or vehicle. After one week, no changes in functional or structural parameters related to kidney damage were observed in STZ group; however, a higher renal expression of proinflammatory cytokines and HSP70 was found. Expression of Steroidogenic Acute Regulatory protein (StAR) and P450scc (CYP11A1) was decreased in STZ kidneys. Incubation of isolated mitochondria with 22R-hydroxycholesterol revealed a marked inhibition in CYP11A1 function at the medullary level in STZ group. The inhibition of these first steps of renal steroidogenesis in early STZ-induced diabetes led to a decreased local synthesis of pregnenolone and progesterone. These findings stimulate investigation of the probable role of nephrosteroids in kidney damage associated with diabetes.